Das imagens das crianças às imagens de ciências: o encontro da infância com a cultura científica - Lacerda Junior, José Cavalcante (2014)
In this sense, the present study aimed to identify the images that children produce about science in a space of Scientific Culture from their experiences. During its development was proposed the following problem: what are the meanings expressed by the children to images of Sciences produced by them through their experiences in a space of Scientific Culture? To that effect, the study is organized in three (03) chapters. In the first chapter, we will present a theoretical framework about the topics Sciences, Culture and infancy highlighting the relationship between them. In the second chapter we will highlight the methodological path traced for this survey, which was conducted with eleven (11) children who expressed nodded and participation in research as well as the permission of their parents. All children attending the course Drawing for Children School of Arts and Crafts Claudio Santoro - LAOCS - Cachoeirinha unit, which is considered an art school. The techniques used in this study included a literature survey, observation and his record in the field diaries, thematic studies and group discussions. Finally, in the third chapter, we describe the results of the survey, which indicate that the construction of the capture of images of Sciences, conducted with children, the process enables the understanding that science emerge from a process that establishes a relationship or is, scientific knowledge contribution is the close reality of the subject, where it appropriates and recreates such knowledge in context. And yet, the need to recognize the environment where research, positing a basic research, where children are heard and understood as partners in the process.